Effect of N-Acetylserotonin on TLR-4 and MyD88 Expression during Intestinal Ischemia-Reperfusion in a Rat Model - Sukhotnik, Igor; Ben Shahar, Yoav; Halabi, Salim; Bitterman, Nir; Dorfman, Tatiana; Pollak, Yulia; Coran, Arnold; Bitterman, Arie (European Journal of Pediatric Surgery, 2019)
Background Accumulating evidence indicates that changes in intestinal toll-like receptors (TLRs) precede histological injury in a rodent model of necrotizing enterocolitis. N-acetylserotonin (NAS) is a naturally occurring chemical intermediate in the biosynthesis of melatonin. A recent study has shown that treatment with NAS prevents gut mucosal damage and inhibits programmed cell death following intestinal ischemia-reperfusion (IR). The objective of this study was to determine the effects of NAS on TLR-4, myeloid differentiation factor 88 (Myd88), and TNF-α receptor-associated factor 6 (TRAF6) expression in intestinal mucosa following intestinal IR in a rat.Materials and Methods Male Sprague-Dawley rats were randomly assigned to one of the four experimental groups: 1) Sham rats underwent laparotomy; 2) Sham-NAS rats underwent laparotomy and were treated with intraperitoneal (IP) NAS (20 mg/kg); 3) IR rats underwent occlusion of both superior mesenteric artery and portal vein for 20 minutes followed by 48 hours of reperfusion; and 4) IR-NAS rats underwent IR and were treated with IP NAS immediately before abdominal closure. Intestinal structural changes, mucosal TLR-4, MyD88, and TRAF6 mucosal gene, and protein expression were examined using real-time PCR, Western blot, and immunohistochemistry.Results Significant mucosal damage in IR rats was accompanied by a significant upregulation of TLR-4, MyD88, and TRAF6 gene and protein expression in intestinal mucosa compared with control animals. The administration of NAS decreased the intestinal injury score, inhibited cell apoptosis, and significantly reduced the expression of TLR-4, MyD88, and TRAF6.Conclusion Treatment with NAS is associated with downregulation of TLR-4, MyD88, and TRAF6 expression along with a concomitant decrease in intestinal mucosal injury caused by intestinal IR in a rat.
Keywords: N-acetylserotonin; intestine; ischemia-reperfusion; toll-like receptor 4; MyD88